(untitled) - Nguyễn, Văn Phúc (Cần Thơ, 2018)
The study was therefore delimited to the following: The teacher's and the student's perceptions of RL in these piloted textbooks; only teachers' and learners' perceptions towards advantages and shortcomings of RL in these student books are investigated and other sections of the books are not included in this study. Only one high school participated in the study with eighty students and two English teachers who taught these two pilot classes formed the study sample.
Keywords: Tiếng Anh,English language; Học và dạy học,Study and teaching